2004
DOI: 10.1103/physrevlett.92.035001
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Advanced Tokamak Plasmas without the Use of an Ohmic-Heating Solenoid

Abstract: A new operational scenario of advanced tokamak formation was demonstrated in the JT-60U tokamak. This was accomplished by electron cyclotron and lower hybrid waves, neutral beam injection, and the loop voltage supplied by the vertical field and shaping coils. The Ohmic heating (OH) solenoid was not used but a small inboard coil (part of the shaping coil), providing less than 20% of total poloidal flux, was used. The plasma thus obtained had both internal and edge transport barriers, with an energy confinement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…(iv) NBCD assisted by bootstrap current using a seed plasma. (v) Inductive drive during a beta ramp, using flux from the vertical field ramp [25,26], a major contribution in an ST.…”
Section: Start-upmentioning
confidence: 99%
“…(iv) NBCD assisted by bootstrap current using a seed plasma. (v) Inductive drive during a beta ramp, using flux from the vertical field ramp [25,26], a major contribution in an ST.…”
Section: Start-upmentioning
confidence: 99%
“…However, as the synchrotron radiation loss is reduced due to the lower toroidal field, the power fraction to ion can be reduced to F ion = 0.6 for obtaining the hot ion mode of T i /T e ∼ 1.5 (see column (2) in Table 1). Thus, we have found that the power fraction to ion should be larger than 0.6 in the D- 3 He MT reactor and the operation regime is not so wide as in a ST as will be seen below.…”
Section: Temporal Evolution Of the Plasma Parameters To Ignitionmentioning
confidence: 97%
“…Recent successful experiments of the plasma current ramp-up by the vertical field and heating power [2,3] encourage parameter studies of D- 3 He spherical tokamak (ST) and medium aspect ratio tokamak (MT) reactors because the large plasma current is necessary for D- 3 He fusion. Additionally, the hot ion mode (T i > T e ) is indispensable to achieve D- 3 He fusion to cope with the synchrotron radiation loss.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the small size of DEMO needs advanced tokamak operation techniques, e.g. a high beta operation to obtain P fus of the order of gigawatt, an advanced non-inductive plasma current ramp-up method [3], and so on. For example, in the design of the compact tokamak fusion DEMO SlimCS, the CS is not used for the plasma ramp-up but for the plasma shape control [4][5][6].…”
Section: Introductionmentioning
confidence: 99%